Variability of soil organic carbon and nutrient content across land uses and agriculturally induced land use changes in the forest-savanna transition zone of Cameroon - Mandah, V.P.; Tematio, P.; Onana, A.A.; Fiaboe, K.K.M.; Arthur, E.; Giweta, M.H.; Ndango, R.; Silatsa, F.B.T.; Voulemo, D.D.I.; Biloa, J.P.; Nguemezi, C.; Masso, C. (Elsevier, 2024)
Data expressing the effects of land use change on soil attributes is still very scarce in Cameroon as in most of Africa. In this regard, this study aimed to assess soil organic carbon (OC), nitrogen (N), phosphorus (P), and potassium (K) content across land uses and agricultural-induced land use changes in the forest-savanna transition zone of Cameroon. Nine land uses were identified in the study area showing five directions of land use changes namely the change from the native forest to cocoa agroforestry, native savannah to cocoa agroforestry, native savannah to cropland, savannah fallow to cropland, and transition zone fallow to cropland. The soil was sampled at 0–10 cm (upper layer) and 10–30 cm (lower layer) depths in three replicates for each land use and analyzed for physicochemical properties. There were significant differences across the land uses for OC (p < 0.02), N (p < 0.01), C/N (p < 0.01), pH (p < 0.02), soil organic carbon stocks (SOCS) (p < 0.01), and soil nitrogen stocks (SNS) (p < 0.01), with a relatively higher magnitude in the upper soil layer. Higher magnitudes of OC (26.1 to 22.5 g kg−1), N (2.5 to 1.6 g kg−1), SOCS (32.1 to 27.8 Mg ha−1), and SNS (2.9 to1.9 Mg ha−1) were observed in native lands and cocoa agroforestry with the highest in the native forest and the forest-based cocoa agroforestry. Meanwhile, the effect of land use change on soil properties was mainly significant in the change from native savannah to croplands at p < 0.05 for OC, N, SOCS, and SNS, and p < 0.02 for P. Therefore, agroforestry is an alternative to enhance the ecological resilience of lands affected by land use changes.